Interpenetrating organic–inorganic network: A short review on aerogel as a nanoporous filler in epoxy nanocomposite. Issue 6 (20th October 2019) - Salimian, Saeed; Zadhoush, Ali; Talebi, Zahra
Abstract: Aerogels are porous solid‐state materials which are composed of a three‐dimensional (3D) solid network with a large number of air‐filled pores in the form of highly crosslinked structures. Because of their characteristics, such as high surface area, large open pores, extremely low density, and favorable interfacial interactions between aerogel and the polymer, they have attracted considerable interest for use as reinforcing agents in polymer composites. Among all aerogel‐polymer composite, epoxy‐based nanocomposites have been widely studied because of their widespread industrial applications. This overview focuses on recent advances concerning silica aerogel‐epoxy nanocomposite and how the aerogel affect measurable properties of epoxy nanocomposite. Herein, the structure of epoxy polymer chains trapped inside the silica aerogel pores has been discussed.